Penerapan Mesin Pencacah Rumput untuk Meningkatkan Efisiensi Usaha Peternakan pada Kelompok Ternak Bumdes - Syaukaty Yasinta; Trio Nur Wibowo; Andri Andriawan; Fadli Sulaeman (JPM: Jurnal Pengabdian Masyarakat, 2025)
The Livestock Group of Bumdes Kridatama in Gumiwang Village, Purbalingga, is a farming cooperative managing beef cattle and goats. Currently, animal feeding practices rely entirely on manually cut fresh grass without further processing. Field observations and interviews indicate that this method is inefficient, requiring 4 to 5 hours per day for grass cutting, and fails to meet optimal nutritional requirements for livestock due to inconsistent grass size and poor digestibility. To address these challenges, a community service program was conducted to improve the members’ knowledge and skills in using a grass chopping machine, aiming to enhance the efficiency of livestock farming operations. The program involved 15 active members of the Bumdes Kridatama Livestock Group as participants. The implementation methods included socialization on the importance of high-quality feed processing, hands-on training in operating the grass chopping machine, and live demonstrations from chopping to feeding the processed grass to livestock. Following implementation, regular monitoring, evaluation, and mentoring were conducted to ensure sustainability. Evaluation results showed a significant improvement in operational efficiency: the average time required for feed preparation decreased from 4.5 hours per day to just 1.1 hours—a reduction of 75.6%. Moreover, the use of finer and more uniform chopped grass improved feed digestibility, leading to a 10–15% increase in livestock weight gain over a three-month period compared to pre-intervention levels. Participants responded positively, with 90% reporting that the machine was easy to operate, and 80% stating that the program helped make their farming activities more efficient and better managed. This initiative demonstrates that the adoption of appropriate technology—specifically, the grass chopping machine—can significantly improve feeding efficiency, enhance animal productivity, and contribute to the sustainable improvement of farmers’ livelihoods.